Molecular Lymphatic Mapping of the Sentinel Lymph Node - Taback, Bret (American Society for Investigative Pathology, 2002)
Intraoperative lymphatic mapping to identify the sentinel lymph node (SLN) has significantly changed the management of regional lymph node basin of patients with various types of solid tumors such as melanoma and breast cancer. The procedure has improved the diagnosis of micrometastasis in the regional tumor-draining lymph nodes by providing a focused histopathological assessment of select lymph nodes most likely to harbor occult disease. Blue dye and/or radioisotopes are efficient mapping agents but the lack of accurate methods to quantify their presence and the potential for dissolution and decay, respectively, throughout time limit their role as reliable markers for identifying a sentinel node from additional secondary lymph nodes that may be either blue and/or radioactive to some degree. A consistently durable marker is needed that can be introduced during surgery and successfully quantitated among tumor-draining lymph nodes to permit a more accurate assessment of hierarchical organization. This may be of particular importance in retrospective analysis of archival tissues as there are no inherent markers to denote the SLN from successive echelon nodes. A procedure of molecular lymphatic mapping (MLM) was developed in a rat model to label the SLN preoperatively with rice gene DNA containing plasmid or linear rice DNA fragment (rDNA). The MLM efficiency was demonstrated by polymerase chain reaction (PCR) detection of the molecular marker in both frozen and paraffin-embedded SLN; 1.25 μg of rDNA injected with blue dye could be reproducibly detected by PCR. The MLM procedure was validated in a rat breast tumor model with lymph node metastasis. The procedure was successful in permanently labeling and identifying by PCR both frozen and paraffin-embedded SLN. MLM in conjunction with a conventional mapping agent can be used as a valuable asset for molecular assessment of the SLN and retrospective analysis of paraffin-embedded specimens.